2000
DOI: 10.1053/he.2000.5921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal cholestasis on bile acid transfer across the rat placenta–maternal liver tandem

Abstract: Cholestasis of pregnancy induces alterations in bile acid transport by human trophoblast plasma membrane (TPM) vesicles. We investigated whether maternal cholestasis affects the overall ability of the rat placenta to carry out vectorial bile acid transfer from the fetus to the mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 35 publications
(50 reference statements)
7
31
0
9
Order By: Relevance
“…Moreover, at least in rodents, bilirubin does not undergo any major biotransformation during its residence in the placenta [104] . The existence of vectorial properties for transplacental bilirubin transfer are consistent with the moderate increases in serum bilirubin concentrations observed in the fetuses of pregnant rats with marked hyperbilirubinemia due to common bile duct ligation [47] . The mechanism for the placental uptake of fetal biliary pigments is not completely understood.…”
Section: Excretion Of Biliary Pigmentssupporting
confidence: 74%
See 2 more Smart Citations
“…Moreover, at least in rodents, bilirubin does not undergo any major biotransformation during its residence in the placenta [104] . The existence of vectorial properties for transplacental bilirubin transfer are consistent with the moderate increases in serum bilirubin concentrations observed in the fetuses of pregnant rats with marked hyperbilirubinemia due to common bile duct ligation [47] . The mechanism for the placental uptake of fetal biliary pigments is not completely understood.…”
Section: Excretion Of Biliary Pigmentssupporting
confidence: 74%
“…The accumulation of bile acids in fetal serum can have serious consequences, depending on the magnitude of the hypercholanemia [45] ; in the most severe cases there is an increased risk of stillbirth and perinatal mortality [46] , while in less severe conditions, maternal hypercholanemia can affect normal fetal development, the liver being one of the tissues most affected [47] . In fact, in a laboratory animal model of maternal hypercholanemia, the repercussions on fetal hepatobiliary function, although reversible, are maintained in young animals [20] , and are characterized by a partial impairment in the ability of the liver to secrete organic anions, whereas the bile acidinduced biliary secretion of phospholipids, but not cholesterol, is increased [20,48] .…”
Section: The Hepatobiliary Excretory Function During Intrauterine Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Among transporters involved, ABCG2, also known as breast cancer resistance protein (BCRP), plays a key role [16]. Previous studies using experimental models of maternal cholestasis in rats [17] have reported an impairment in the placental transfer of bile acids due to trophoblast atrophy and a lack of apical membrane microvilli. This damage was partially prevented by UDCA administration [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies have already addressed the issue of the effect of maternal cholestasis on foetal bile acid homeostasis in humans [19] or in animal models [17,18], the whole picture is incomplete, which has prompted us to investigate further the impairment in bile acid homeostasis in the mother-placenta-foetus trio during ICP. We have also addressed the question of whether removal of PMS is included among the mechanisms of action accounting for the beneficial effect of UDCA in ICP.…”
Section: Introductionmentioning
confidence: 99%